The Duration of New Job Matches in East and West Germany - Joachim Wolff (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2004)
This study compares the duration of new job matches in the east and west German labour market that formed between the start of the German Economic, Monetary and Social Union in July 1990 and December 2000. The study relies on job duration data drawn from the German Socio-economic Panel. It shows with non-parametric duration methods that job matches are less stable in east than in west Germany. However, this is not the case in the first years of the transition process, in which most likely the more profitable jobs were created and the best job matches were formed. Results form the non-parametric analysis but also from a proportional hazards model that controls for important covariates imply that the transition rates into alternative jobs and into unemployment vary with tenure in a way, which is in line with predictions of theories of job mobility such as the job specific capital hypothesis and matching theories.
urn:nbn:de:bvb:19-epub-360-2
Keywords: C41; J63; P52; 330; Job duration; job changes; hazard rate; theories of job mobility; economies in transition